The potential impact of an anti-stigma intervention on mental health help-seeking attitudes among university students - Shahwan, Shazana (2021)
Background: The reluctance of young adults to seek mental health treatment has been attributed to poor mental health literacy, stigma, preference for self-reliance and concerns about confidentiality. The purpose of this study was to examine the potential impact of an anti-stigma intervention that includes education about depression, information about help-seeking as well as contact with a person with lived experience, on help seeking attitudes. Methods: A pre-post study design was employed. Changes in help-seeking attitudes were measured using the Inventory of Attitudes towards Seeking Mental Health Services (IASMHS) immediately post-intervention and after 3 months. Sociodemographic data, information on past experiences in the mental health field and contact with people with mental illness were collated. Three hundred ninety university students enrolled in the study. Linear mixed models were used to examine the effects of the intervention. Results: Scores on all subscales of the IASMHS, Psychological Openness (PO), Help-seeking Propensity (HP) and Indifference to Stigma improved significantly post-intervention and at 3-month follow-up compared to pre-intervention, with HP demonstrating the highest effect size. However, a significant decline was observed on all three scales at 3-month follow-up compared to post-intervention. Gender, having friends/family with mental illness, and previous experience in the mental health field moderated the intervention effects for the PO and HP subscales. Conclusions: The study showed that the brief anti-stigma intervention was associated with improvements in help-seeking attitudes among university students with differential effects among certain sub-groups. As the beneficial outcomes appeared to decrease over time, booster sessions or opportunities to participate in mental health-related activities post-intervention may be required to maintain the desired changes in help-seeking attitudes.